Optimal promotion planning for a product launch in the presence of word-of-mouth - Bigdellou, Saeide; Aslani, Shirin; Modarres, Mohammad (Journal of retailing and consumer services, 2022)
Marketing managers concern that Word-of-Mouth (WOM) can affect the efficiency of sales promotion policy. Sales promotion might also amplify the strength of WOM which further complicates decision-making. In this study, we deploy an agent-based simulation optimization framework to find an efficient sales promotion plan in the presence of WOM for launching re-purchasable products. In this model, consumers' purchase decisions are influenced by price history, availability and satisfaction of the consumers, and positive/negative WOM. We show that taking WOM on board while determining the promotion plan can significantly increase the net present value. However, amplifying WOM might damage the firm's profit for some product categories.